Project-based Learning to Promote High School Students Descriptive Writing - Ardiana Ardiana; Ariana Ariana; Eka Irianti (UNIB Press, 2023)
In high school, EFL learners are supposed to have the capability of writing a good descriptive text as one of the demand of the curriculum. However, many students still experience problems in producing a successful writing. This study aims at promoting high school students’ writing skills, particularly in writing descriptive text, by utilizing project-based learning. This study employed a Classroom Action Research through two cycles which include planning, acting, observing, and evaluating stages. The data were collected from 23 students of X IIS 4 class of SMA Negeri 4 Takalar as the study subjects by using writing tests and observation. The results of the study show that there was an improvement in students’ scores and behaviour when learning with project-based approach. In the diagnostic test, the students mean score was 65.57. The score improved by 9.9% in cycle I and 13.81% in cycle II to 72.09 and 82.04, respectively. Besides, in the pretest, only five students who can achieve the minimum completeness criteria, but in the end of cycle 2, twenty students can pass the minimum score. In addition, students become more actively engaged in the learning process as they are enthusiastic with the projects given by the teacher. This means that the use of project-based learning gave positive impact to students’ learning to write descriptive paragraphs and teachers are suggested to use it in teaching in EFL writing classrooms.